A male with a de novo translocation involving loss of 15q11q13 material and Prader-Willi syndrome. Issue 6 (June 1994) - Vickers, S; Dahlitz, M; Hardy, C; Kilpatrick, M; Webb, T
Abstract : A male proband is described who carries a de novo translocation between chromosomes Y and 15 associated with Prader-Willi syndrome. In situ hybridisation and molecular studies were used to show loss of the paternally derived 15q11q13 region in the translocated chromosome. Lack of further symptoms indicate that this region was lost with no apparent deletion of the Y chromosome.